Tau Depletion in APP Transgenic Mice Attenuates Task-Related Hyperactivation of the Hippocampus and Differentially Influences Locomotor Activity and Spatial Memory - Yoshikawa, Misato; Soeda, Yoshiyuki; Michikawa, Makoto; Almeida, Osborne F. X.; Takashima, Akihiko (Frontiers in Neuroscience, 2018)
Hippocampal hyperactivity, ascribed to amyloid β (Aβ)-induced imbalances in nerual excitation and inhibition, is found in patients with mild cognitive impairment, a prodromal stage of Alzheimer’s disease (AD). To better understand the relationship between hippocampal hyperactivity and the molecular triggers of behavioral impairments in AD, we used Mn-enhanced MRI (MEMRI) to assess neuronal activity after subjecting mice to a task requiring spatial learning and memory. Depletion of endogenous tau in an amyloid precursor protein (APP) transgenic (J20) mouse line was shown to ameliorate hippocampal hyperactivity in J20 animals, tau depletion failed to reverse memory deficits associated with APP/ Aβ overproduction. On the other hand, deletion of tau alleviated the hyperlocomotion displayed by APP transgenics, suggesting that the functional effects of Aβ-tau interactions reflect the temporal appearance of these molecules in individual brain areas.